2014
DOI: 10.1159/000368234
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Blood and Body Fluids among Health-Care Workers in Serbia

Abstract: Objectives: The aim of this study was to examine the epidemiology of occupational accidents and self-reported attitude of health-care workers (HCWs) in Serbia. Subjects and Methods: A cross-sectional study was conducted among HCWs in selected departments of five tertiary care hospitals and in one secondary care hospital in February 2012. A previously developed self-administered questionnaire was provided to HCWs who had direct daily contact with patients. χ2 test and Student's t test were used for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
4
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 22 publications
7
32
4
11
Order By: Relevance
“…Studies have shown that needle-sticks are the leading cause of sharp object injuries [7,10,11,13,14] . In our study, needles were involved in most (72.9%, n=27) of the injuries reported to the ICC, and 33% (n=9) of these injuries occurred during needle recapping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that needle-sticks are the leading cause of sharp object injuries [7,10,11,13,14] . In our study, needles were involved in most (72.9%, n=27) of the injuries reported to the ICC, and 33% (n=9) of these injuries occurred during needle recapping.…”
Section: Discussionmentioning
confidence: 99%
“…According to World Health Organization estimates, the scope of immunization ranges from 18% (in Africa) to 77% (in Australia and New Zealand) [23] . In some studies, the vaccination rate has been reported as 36.6% [15] and 56% [14] . The rate of 35.11% (n=158) seen in our hospital was considered close to World Health Organization estimates and it is apparent that more extensive work is needed to ensure the eradication of HBV.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that healthcare workers whose working hours were greater than 40 hours were at higher risk of sustaining occupational exposure to HIV through percutaneous injuries and mucocutaneous contaminations compared with other healthcare workers is not unique as similar study reported same in Mongolia [21]. This is because fatigue and exhaustion could lead to lack of concentration and can further predispose the healthcare worker to occupational exposure.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, we found that healthcare worker whose working hours was greater than 40 hours were at higher risk of sustaining occupational exposure to HIV through percutaneous injuries and mucocutaneous contaminations compared with other healthcare worker is not unique as similar study reported same in Mongolia [21]. This is because fatigue and exhaustion could lead to lack of concentration and can further predispose the healthcare worker to occupational exposure.…”
Section: Discussionmentioning
confidence: 64%